Capital Structure and Governance Mechanisms External to the Firm: A Cross-Country Analysis - Flávia F. P. Mendonça; Henrique Castro Martins; Paulo R. S. Terra (RAC: Revista de Administração Contemporânea, 2019)
This study investigates whether governance mechanisms external to the firm affect leverage using a sample of 7.490 companies from 40 countries. Our contribution is to separate mechanisms that protect minority shareholders from those that protect creditors rights. Our results show that companies issue debt following the Pecking Order Theory (POT). We find that both mechanisms protecting shareholders and creditors affect corporate leverage. When protection is high, companies issue less debt. Our results are robust to several alternative specifications and variations in our model. We interpret our results as evidence that, when investors are well protected, firms issue less debt, possibly to avoid the monitoring role of debt over the discretion of insiders.